A competitive analysis for the Start-Gap algorithm for online memory wear leveling - Devanny, William E.; Goodrich, Michael T.; Irani, Sandy (Information processing letters, 2021)
•This paper presents a novel competitive analysis of the Start-Gap wear-leveling algorithm.•Under reasonable assumptions, w.h.p., Start-Gap can serve (1−o(1))NL write requests before writing to a location more than L times.•The analysis implies a competitive ratio of 1/(1−o(1)) for Start-Gap. Erase-limited memory, such as flash memory and phase change memory (PCM), has limitations on the number of times that any memory cell can be erased. The Start-Gap algorithm has shown a significant ability in practice to distribute updates across the cells of an erase-limited memory, but it has heretofore not been characterized in terms of its competitive ratio against an optimal offline algorithm that is given all the update addresses in advance. In this paper, we present a competitive analysis for the Start-Gap wear-leveling algorithm, showing that under reasonable assumptions about the sequence of update operations, the Start-Gap algorithm has a competitive ratio of 1/(1−o(1)).